Analysis of interrelationships between the management of agricultural water consumption optimization constructs based on smart climate agriculture: application of structural analysis - Ali Tavasoti; Mehrdad Niknami; Jamal Farajollah Hosseini; Maryam Omidi Najafabadi (Frontiers in Climate)
Considering that the behavior of farmers regarding the use of smart climate agricultural technologies is influenced by the socio-economic conditions of their locality, this study identified the constituent components of optimal agricultural water consumption management in Pakdasht city, Iran. To analyze the data, structural equation modeling (SEM) was employed using AMOS20 to investigate the linear relationships between latent and explicit variables. The results showed that the hidden variables of educational and economic, technical and economic, and cultural and economic dimensions have a significant relationship with each other. Variables such as financial support from official institutions to greenhouse owners for the preparation and installation of new irrigation systems, financial facilities provided by Agriculture Bank for greenhouse development, financial support for research and development in optimal water management, and financial support packages for adopters of smart technologies impact the economic dimension of water consumption management among greenhouse owners. Additionally, the ability to attract support from local leaders for optimal water management, capacity building, and the empowerment of local communities—particularly youth—in this area, as well as the formation of cooperative groups among users of new irrigation methods, facilitate interactions between greenhouse owners.